Safety and efficacy of underwater versus conventional endoscopic mucosal resection for colorectal polyps: Systematic review and meta-analysis of RCTs - Chandan, Saurabh; Bapaye, Jay; Khan, Shahab R.; Mohan, Babu P.; Ramai, Daryl; Dahiya, Dushyant S.; Bilal, Mohammad; Draganov, Peter V.; Othman, Mohamed O.; Rodriguez Sánchez, Joaquin; Kochhar, Gursimran S. (Endoscopy International Open, 2023)
Background and study aims Conventional endoscopic mucosal resection (C-EMR) is limited by low en-bloc resection rates, especially for large (> 20 mm) lesions. Underwater EMR (U-EMR) has emerged as an alternative for colorectal polyps and is being shown to improve en-bloc resection rates. We conducted a systematic review and meta-analysis comparing the two techniques.Methods Multiple databases were searched through November 2022 for randomized controlled trials (RCTs) comparing outcomes of U-EMR and C-EMR for colorectal polyps. Meta-analysis was performed to determine pooled proportions and relative risks (RRs) of R0 and en-bloc resection, polyp recurrence, resection time, and adverse events.Results Seven RCTs with 1458 patients (U-EMR: 739, C-EMR: 719) were included. The pooled rate of en-bloc resection was significantly higher with U-EMR vs C-EMR, 70.17% (confidence interval [CI] 46.68–86.34) vs 58.14% (CI 31.59–80.68), respectively, RR 1.21 (CI 1.01–1.44). R0 resection rates were higher with U-EMR vs C-EMR, 58.1% (CI 29.75–81.9) vs 44.6% (CI 17.4–75.4), RR 1.25 (CI 0.99–1.6). For large polyps (> 20 mm), en-bloc resection rates were comparable between the two techniques, RR 1.24 (CI 0.83–1.84). Resection times were comparable between U-EMR and C-EMR, standardized mean difference –1.21 min (CI –2.57 to –0.16). Overall pooled rates of perforation, and immediate and delayed bleeding were comparable between U-EMR and C-EMR. Pooled rate of polyp recurrence at surveillance colonoscopy was significantly lower with U-EMR than with C-EMR, RR 0.62 (CI 0.41–0.94).Conclusions Colorectal U-EMR results in higher en-bloc resection and lower recurrence rates when compared to C-EMR. Both techniques have comparable resection times and safety profiles.
Keywords: Endoscopy Upper GI Tract; Precancerous conditions & cancerous lesions (displasia and cancer) stomach; Endoscopic resection (ESD, EMRc, ...); Polyps/adenomas/ ...; Colorectal cancer